Peningkatan Pengetahuan Masyarakat tentang Bahaya Paparan Mikroplastik dan Dampaknya bagi Kesehatan - Ilmiawati Ilmiawati; Liganda Endo Mahata; Gestina Aliska; Erlina Rustam; Yusticia Katar; Rahmatini Rahmatini; Julizar Julizar; Elly Usman (Warta Pengabdian Andalas, 2022)
Plastic is a global problem; plastic pollution production reaches 350 million tons annually. This plastic pollution will be degraded into microplastic. This microplastic will pollute the environment and negatively impacted health if exposed too much. Recent research has found microplastics in clothes, toys, and even food. The Department of Pharmacology and Therapeutics, Faculty of Medicine, Universitas Andalas conducts outreach to the public to enhance the general public's understanding of microplastics and their impact on health. The outreach activity began with filling out a pre-test to assess the public's understanding of microplastics. Followed by education about microplastic exposure, the dangers of microplastics, and education about a healthy lifestyle to reduce sources of microplastic exposure. The event ended with filling out a post-test by participants. Paired t-test analysis on pre-test and post-test data showed an increase in public understanding regarding microplastics, sources of exposure, health impacts and ways to reduce microplastic exposure. Based on these results, it can be concluded that the provision of public service can increase public understanding regarding the sources of microplastics and their impact on health and encourage people to live a healthy lifestyle that minimizes exposure to microplastics.